Effect of Eco-Friendly Chemical Treatment on the Properties of Sesbania Rostrata Fiber. Issue 12 (2nd December 2021) - Raja, K.; Senthilkumar, P.; Nallakumarasamy, G.; Natarajan, T.
ABSTRACT: Green material consciousness has enthused to introduce natural fiber alternative to man-made fiber as reinforcement in polymer composites. The presence of surface impurities and non-cellulosic component in the natural fibers are the major limitations to form effective polymer composite due to lack of interfacial bonding. This can be prevailed by various physical and chemical treatments. The present work reports the effect of chemical treatment on physical, chemical, mechanical, and thermal properties of Sesbania rostrata fibers (SRFs) by commercial sodium bicarbonate (NaHCO3 ), commonly known as 'baking soda.' The SRFs are treated with 10%w/w of NaHCO3 for the different duration (1, 3 and 5 days) at room temperature. The treated fiber shows high and improved mechanical strength and cellulose fraction. The results of X-ray diffraction and thermogravimetric analysis revealed that the crystallinity index and thermal stability are increased for the treated fiber. The significant removal of hemicellulose in the treated fiber is also observed from the FT-IR characteristic curve. The scanning electron microscopy images exposed the presence of rough surface on the treated fibers. Further, the comparison of treatment results showed that 3 days duration is the optimum period for treating the SRFs.